Investigating the impacts of a changing climate on the risk of overheating and energy performance for a UK retirement village adapted to the nZEB standards. (July 2019) - Salem, Radwa; Bahadori-Jahromi, Ali; Mylona, Anastasia
The death toll of the 2003 heat wave in Europe exceeded 35, 000 heat-related deaths. The elderly population were the most affected. The current paradigm within the construction industry in cold-dominant countries is to design/retrofit buildings with high levels of insulation. Whilst thermal comfort may be reached during colder months with this approach, the risk of overheating can be increased during hotter months. This paper aims to examine the impacts of a changing climate on the risk of overheating and energy performance for a UK retirement village. For this study, the buildings within the retirement village will be designed to reach the nearly zero energy building standard. Consequently, the risk of overheating of the buildings within the retirement village as they currently stand and as zero energy buildings will be investigated under current and future climatic conditions. The analysis is carried out using thermal analysis simulation software (TAS, Edsl). Combined heat and power and combined cooling, heat and power will be investigated as mitigating strategies with regard to overheating. The results of this study do not undermine the importance of continuing to improve the energy efficiency of existing buildings but rather highlight that the approach undertaken should be reconsidered. Practical application : Currently, there is emphasis placed on retrofitting and designing buildings, with high energy efficiency standards. Whilst this is in line with our vision as a society towards reaching a decarbonised, sustainable future, this work highlights that doing so, carries risks with regard to overheating. Nonetheless, the results demonstrate that with the incorporation of suitable mitigation strategies and adequate ventilation strategies, it is possible to achieve an energy efficient building that meets the heating and cooling demand (and thereby thermal comfort of occupants) during the heating and non-heating season.